Seasonal variability and fluxes of nitrate in the surface waters over the Arctic shelf slope - Randelhoff, Achim; Sundfjord, Arild; Reigstad, Marit (UiT The Arctic University of Norway, 2015)
Poster presentation from Polar Marine Science (Gordon Research Conference), Lucca, March 2015. Understanding the present state and possible future scenarios of Arctic Ocean primary productivity has been hampered by the scarcity of year-round nutrient measurements. Here, the first year-long moored timeseries of near-surface nitrate concentrations in the Eastern Arctic, together with hydrography, currents and chlorophyll-a fluorescence, is reported from the shelf slope north-east of Svalbard.